Implementation of Interactive Learning Media Based on Virtual Laboratory to Improve Students Science Literacy Skills - Daud, Manda Nur Aisia; Abdjul, Tirtawaty; Payu, Citron S.; Ntobuo, Nova Elysia; Odja, Abdul Haris; Nurhayati, Nurhayati (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Virtual laboratories based on computers allow students to conduct practical work or experiments with real phenomena or laboratory equipment sets. This study aims to test the implementation of interactive learning media based on virtual laboratories on the topic of substances and their changes to students' scientific literacy skills. This study was conducted in class VII of SMP Negeri 1 Tilongkabila and SMP Negeri 4 Tilamuta in the 2024/2025 Academic Year. The research design used A one-group pre-test and a post-test design involving three classes as samples. The study results showed a significant increase in students' scientific literacy skills after treatment using virtual laboratory media based on PhET Simulation. PhET Simulation media allow students to conduct experiments virtually, improving students' understanding of abstract concepts and thinking skills. The results indicate this through the hypothesis testing criteria where T-count ≥ T-table with a level of ∝ = 0.05 for the experimental and replication classes 1 in each school; therefore, H0 is rejected, and H1 is accepted. So, it can be concluded that there is an effect of implementing interactive learning media based on a virtual laboratory on the scientific literacy skills of junior high school students on the topic of substances and their changes. Meanwhile, normalized gain for all sample classes, both experimental and replication, which are in the high category, in the experimental class at SMP Negeri 1 Tilongkabila (0.75), the experimental class at SMP Negeri 4 Tilamuta (0.79) and the replication class 1 (0.83). So, it can be concluded that there is an effect of implementing interactive learning media based on a virtual laboratory on the scientific literacy skills of junior high school students on the topic of substances and their changes.